Stress and Coping Strategies of Madrasah’s Teachers on Applying Distance Learning During COVID-19 Pandemic in Indonesia - Siti Muawanah; Umi Muzayanah; Moses G. R. Pandin; Mochamad D. S. Alam; Januari P. N. Trisnaningtyas (Qubahan Academic Journal)
The COVID-19 pandemic has changed many aspects of life, including face-to-face learning processes in madrasah to distance learning. These changes have caused psychological problems or stress among teachers. The study aims to describe the mental health issue during COVID-19 and how to overcome it. The study applied quantitative and qualitative approaches, with 1,520 teachers, consisting of 615 teachers from Islamic Schools (madrasah) in Bali and 905 in NTT. Findings indicate that the stress level experienced by madrasah teachers in the two provinces was in a low category at a score of 1.54, though both regions were at very different levels in terms of internet affordability, the highest cause of teacher stress was the concern for students’ ability to absorb the learning material; and 92.68% of teachers selected problem-focused coping mechanisms, particularly efforts to improve their skills in conducting distance learning. The findings from the study provide important input for teachers’s coping strategies for mental health issues of distance learning.